TYPES OF DOMESTIC VIOLENCE EXPERIENCED BY WOMEN IN ABUSIVE RELATIONSHIPS - Ilze Slabbert; Sulina Green (Social Work/Maatskaplike Werk, 2013)
Research and specialised practice indicate that women who are abused by their intimate partners are at an increasing risk the longer the abuse continues. Many men show escalating violent behaviour toward their female partners and many women are killed by their partners (Roche, 1999:24). Several researchers (Artz, 1999:2; Damon, 2003:94; Flinck, Paavilainen & Asredt-Kurki, 2005:383; Gelles, 1999:168; Vincent & Jouriles, 2002:7) view domestic violence as a leading cause of female injury in almost every country. Dwyer, Smokowski, Bricout and Wodarski (1995:185) claim that injuries as a result of domestic violence are more common than from muggings, car accidents and death resulting from cancer combined